Sexual harassment: a reference handbook - Smith, Merril D. (Contemporary world issues, 2020)
"Providing an indispensable resource for high school and college readers investigating sexual harassment in the United States, Sexual Harassment: A Reference Handbook is a comprehensive summary of history, current events, possible solutions, and resources"--